Value Determination of Supply Chain Initiatives A Quantification Approach Based on Fuzzy Logic and System Dynamics - Wessely, Philip; SpringerLink (Online service) (Wiesbaden : Gabler, 2011)
The implementation of supply chain initiatives (SCI) often requires specific investments in technology, material, organization and staff. However, the assessment of the economic viability of such inter-organizational activities is not a trivial issue. Philip Wessely supports managerial decision-making in the forefront of a potential implementation by introducing a quantification approach for the value contribution of SCIs. The resulting approach combines different innovative modeling techniques and considers the individual integration of companies in inter-organizational networks. As a result, it has a broad field of application.
Keywords: Economics; Economics/Management Science; Operations Research/Decision Theory